Effects of low mobility of the spine in young male and female wrestlers - Ioannidou, V.; Makri, E.; Barbas, I. (International Journal of Wrestling Science, 2019)
Little research has been done on the effects of flexibility, especially in the spine, but also shoulder and the pelvic girdle and to what extent it affects wrestling. What is the role of these factors and posture in preventing injuries and thus the overall performance of the athlete?